2005
DOI: 10.1002/path.1827
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of Reg IV in human neoplastic and non‐neoplastic tissues: Reg IV expression is associated with intestinal and neuroendocrine differentiation in gastric adenocarcinoma

Abstract: Regenerating islet-derived family, member 4 (Reg IV) is a candidate marker for cancer and inflammatory bowel disease. In the present study, immunohistochemical analysis of Reg IV was performed in various human neoplastic (n = 289) and non-neoplastic tissues. In the stomach, foveolar epithelium was negative for Reg IV, whereas goblet cells of intestinal metaplasia and neuroendocrine cells at the base of intestinal metaplasia expressed Reg IV. Neuroendocrine cells of the small intestine and colon showed strong e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
172
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(194 citation statements)
references
References 24 publications
21
172
1
Order By: Relevance
“…Immunohistochemical Patterns of REG4 Expression in IPMNs According to Morphological Phenotype REG4 expression was detected in islet cells of Langerhans as previously reported, 14 and these were considered to be internal positive controls. However, REG4 expression was not detected in normal pancreatic ductal epithelium, acini and stromal fibroblasts.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Immunohistochemical Patterns of REG4 Expression in IPMNs According to Morphological Phenotype REG4 expression was detected in islet cells of Langerhans as previously reported, 14 and these were considered to be internal positive controls. However, REG4 expression was not detected in normal pancreatic ductal epithelium, acini and stromal fibroblasts.…”
Section: Resultsmentioning
confidence: 92%
“…15,18 REG4 is also detected in goblet cells of intestinal metaplasia of the stomach, which is associated with CDX2. 14 The proliferative activity of the goblet cells is higher in the intestinal metaplasia of the stomach compared to those in the small intestine and colon. 19 The biological and clinical significance of the occurrence of the 'intestinal' pathway of carcinogenesis of IPMN remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative reverse transcription-polymerase chain reaction (PCR) analysis revealed that approximately 50% of GCs overexpress the REG4 gene . Although various normal tissues express REG4 (Hartupee et al, 2001), the levels of expression are much lower in normal tissues than in cancerous tissues (Oue et al, 2005). We reported previously that Reg IV is expressed in GC cells but not stromal cells.…”
Section: Introductionmentioning
confidence: 85%
“…Reg IV was expressed in 30% of GC tissues and was associated with both the intestinal mucin phenotype and neuroendocrine differentiation. In CRC, expression of Reg IV was observed in 36% of cases and was associated with tumor stage (Oue et al, 2005). Furthermore, because it is a secreted protein, Reg IV may be a serum biomarker for GC; however, the concentration of Reg IV in serum has not been investigated.…”
Section: Introductionmentioning
confidence: 99%